A Three‐Photon Active Organic Fluorophore for Deep Tissue Ratiometric Imaging of Intracellular Divalent Zinc. Issue 10 (5th April 2016) - Philips, Divya Susan; Sreejith, Sivaramapanicker; He, Tingchao; Menon, Nishanth Venugopal; Anees, Palapuravan; Mathew, Jomon; Sajikumar, Sreedharan; Kang, Yuejun; Stuparu, Mihaiela Corina; Sun, Handong; Zhao, Yanli; Ajayaghosh, Ayyappanpillai
Abstract: Deep tissue bioimaging with three‐photon (3P) excitation using near‐infrared (NIR) light in the second IR window (1.0–1.4 μm) could provide high resolution images with an improved signal‐to‐noise ratio. Herein, we report a photostable and nontoxic 3P excitable donor‐π‐acceptor system (GMP) having 3P cross‐section ( σ 3 ) of 1.78×10 −80  cm 6  s 2  photon −2 and action cross‐section ( σ 3 η 3 ) of 2.31×10 −81  cm 6  s 2  photon −2, which provides ratiometric fluorescence response with divalent zinc ions in aqueous conditions. The probe signals the Zn 2+ binding at 530 and 600 nm, respectively, upon 1150 nm excitation with enhanced σ 3 of 1.85×10 −80  cm 6  s 2  photon −2 and σ 3 η 3 of 3.33×10 −81  cm 6  s 2  photon −2 . The application of this probe is demonstrated for ratiometric 3P imaging of Zn 2+ in vitro using HuH‐7 cell lines. Furthermore, the Zn 2+ concentration in rat hippocampal slices was imaged at 1150 nm excitation after incubation with GMP, illustrating its potential as a 3P ratiometric probe for deep tissue Zn 2+ ion imaging. Abstract : Shining bright : A new three‐photon (3P) active organic fluorophore with a high 3P absorption cross section close to that of inorganic‐semiconductor‐based systems is reported, which allows deep tissue ratiometric imaging of Zn 2+ in hippocampal slices.